2016
DOI: 10.1093/rpd/ncw059
|View full text |Cite
|
Sign up to set email alerts
|

Study of Radiation Exposure Due to Radon, Thoron and Their Progeny in the Indoor Environment of Rajpur Region of Uttarakhand Himalaya

Abstract: In the present study, the measurements of indoor radon, thoron and their progeny concentrations have been carried out in the Rajpur region of Uttarakhand, Himalaya, India by using LR-115 solid-state nuclear track detector-based time-integrated techniques. The gas concentrations have been measured by single-entry pin-hole dosemeter technique, while for the progeny concentrations, deposition-based Direct Thoron and Radon Progeny Sensor technique has been used. The radiation doses due to the inhalation of radon, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Except for A a TnP and F Rn , W/S values for other thoron parameters were markedly lower than those for the related radon parameters. Activity concentrations of radon, thoron, and their short-lived products in wintertime, together with their W/S ratio, obtained in India, are also reported for 96 dwellings in Hamirpur district, Himachal Pradesh [211], 35 dwellings in Pauri Garhwal, Uttarakhand, Himalaya [45], 27 dwellings in Yamuna and Tons valleys, Garhwal, Himalaya [49], and 25 dwellings in Rajpur region, Uttarakhand, Himalaya [209]. The values are similar to those in Table 6 for the related parameters.…”
Section: Temporal Variations In Radon and Thoron Levels In Indoor Airmentioning
confidence: 73%
See 1 more Smart Citation
“…Except for A a TnP and F Rn , W/S values for other thoron parameters were markedly lower than those for the related radon parameters. Activity concentrations of radon, thoron, and their short-lived products in wintertime, together with their W/S ratio, obtained in India, are also reported for 96 dwellings in Hamirpur district, Himachal Pradesh [211], 35 dwellings in Pauri Garhwal, Uttarakhand, Himalaya [45], 27 dwellings in Yamuna and Tons valleys, Garhwal, Himalaya [49], and 25 dwellings in Rajpur region, Uttarakhand, Himalaya [209]. The values are similar to those in Table 6 for the related parameters.…”
Section: Temporal Variations In Radon and Thoron Levels In Indoor Airmentioning
confidence: 73%
“…Reports on the temporal variation of thoron activity concentration are modest in comparison to that of radon. In addition, reports on seasonal variations of activity concentrations of radon and thoron short-lived products have appeared only recently [45,49,50,166,209].…”
Section: Temporal Variations In Radon and Thoron Levels In Indoor Airmentioning
confidence: 99%
“…The prominent source for residential radon is the soil/rock beneath the dwelling [5]. The earlier studies on indoor radon levels and analysis of its variation were found to be influenced by the factors such as geology, types of building materials used for the construction of dwellings [6][7][8][9]. In addition, ventilation rates, air circulation, temperature and pressure gradient etc., play a vital role in accumulation of radioactive gas in indoor environment [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%